Efficacy and Safety of TangWang Prescription for Type 2 Non-Proliferative Diabetic Retinopathy: A Study Protocol for a Randomized Controlled Trial - Jin, De; Zhang, Yuehong; Zhang, Yuqing; Huang, Wenjing; Meng, Xiang; Yang, Fan; Bao, Qi; Zhang, Meizhen; Yang, Yanan; Ni, Qing; Lian, Fengmei; Tong, Xiaolin (Frontiers in Pharmacology, 2021)
Background: Diabetic retinopathy (DR) is one of the most common and serious microvascular complications of diabetes mellitus (DM), which results in blindness among adults worldwide. Presently, the efficacy of drug treatments for diabetic retinopathy (DR) is not satisfactory, thus urgently necessitating effective drug treatment measures. TangWang prescription (TWP) has been found to have retinal protection effects in previous clinical and basic research. However, there is a lack of rigorous, randomized, and controlled studies. This study aims to evaluate the efficacy and safety of TWP in delaying the development of DR. Methods: This study is a randomized, double-blind, placebo-controlled, parallel-group, multicenter clinical trial, consisting of 384 participants to be randomized in a 1:1 ratio in the treatment and control groups. Furthermore, the treatment and control groups will be administered the TangWang prescription and the placebo, respectively, each at a dose of one bag twice a day. The study period will last for 48 weeks. The primary outcome measure will be the changes in the degree of retinal microvascular lesions before and after treatment. The secondary outcome will be changes in the degree of hemangioma, microvascular bleeding, microvascular leakage, macular edema, and vision. All statistical tests will be two-sided, and a P<0.05 will be considered statistically significant. Discussion: We hypothesize that the patients with DR will benefit from TangWang prescription, and in addition to the central random system and platform of dynamic information collection, the patients’ conditions will be monitored, and the data collected for analysis. If successful, this study will provide evidence that the TCM formulation delays the development of DR.